A kpc-scale-resolved study of unobscured and obscured star formation activity in normal galaxies at z = 1.5 and 2.2 from ALMA and HiZELS. Issue 4 (2nd October 2020) - Cheng, Cheng; Ibar, Edo; Smail, Ian; Molina, Juan; Sobral, David; Escala, Andrés; Best, Philip; Cochrane, Rachel; Gillman, Steven; Swinbank, Mark; Ivison, R J; Huang, Jia-Sheng; et al.
ABSTRACT: We present Atacama Large Millimeter/Submillimeter Array (ALMA) continuum observations of a sample of nine star-forming galaxies at redshifts 1.47 and 2.23 selected from the High- z Emission Line Survey (HiZELS). Four galaxies in our sample are detected at high significance by ALMA at a resolution of 0${_{.}^{′′}}$ 25 at rest-frame 355 μm. Together with the previously observed H α emission, from adaptive optics-assisted integral-field-unit spectroscopy (∼0${_{.}^{′′}}$ 15 resolution), and F606W and F140W imaging from the Hubble Space Telescope (∼0${_{.}^{′′}}$ 2 resolution), we study the star formation activity, stellar and dust mass in these high-redshift galaxies at ∼kpc-scale resolution. We find that ALMA detection rates are higher for more massive galaxies ( M * > 10 10.5 M⊙ ) and higher [N ii ]/H α ratios (>0.25, a proxy for gas-phase metallicity). The dust extends out to a radius of 8 kpc, with a smooth structure, even for those galaxies presenting clumpy H α morphologies. The half-light radii ( R dust ) derived for the detected galaxies are of the order ∼4.5 kpc, more than twice the size of submillimetre-selected galaxies at a similar redshift. Our global star formation rate estimates – from far-infrared and extinction-corrected H α luminosities – are in good agreement. However, the different morphologies of the different phases of the interstellar medium suggest complex extinction properties of the high-redshift normal galaxies.